ANALISIS PIUTANG TERHADAP LIKUIDITAS PERUSAHAAN - Rahmawati, Ita Nur (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2013)
Analysis and Collection of Accounts Receivable AccountsReceivable Turnover on Corporate Liquidity at CV.JI Semarang, thisstudy aims to determine the level of turnover and the collection ofaccounts receivable against the debtor that occurred in 2011, 2012 and2013. Liquidity So the company can be found at any period ofdevelopment. This research used to collect financial statementsconsisting of the balance of the year 2011, 2012 and 2013. Analyticaltool used in this study is the accounts receivable turnover, collectingreceivables and liquidity. Data collection techniques used in the studywere interviews with company directors and administrative staff of oneof the debtor company experienced problems in payment.The results of the analysis can be drawn that the company is lessefficient in running their business. It can be seen that the developmentand collection of accounts receivable turnover tends to decline during theyears 2011, 2012, and 2013. This is due to the company's ability tomanage its accounts receivable less well and always has decreased andthe increase from year to year.From the analysis above it can beconcluded that the company was not able to maintain stable liquidity(ability) in the company's financial management. So in the last year ofthe study, in 2013 the company threatened bankruptcy because of capitalrelated to doubtful accounts is too high.